RELEVANSI KONSEP KEBAHAGIAAN PERSPEKTIF ABU-NASHR AL-FARABI DI ERA DIGITAL (SUNGKAI: Jurnal Aqidah dan Filsafat Islam, 2025)
The search for happiness in the digital age is increasingly complex due to rapid social, cultural, and technological changes. Social media, the unlimited flow of information, and the pressures of a modern lifestyle often lead to identity crises and life dissatisfaction. In this context, Al-Farabi's thoughts on the concept of happiness become relevant as a guide to achieving spiritual and intellectual well-being. Al-Farabi emphasized the importance of intellectual perfection, character development, and harmonious relationships with society as the path to true happiness. This research employed a qualitative approach with literature review and historical-descriptive analysis. Data were obtained from Al-Farabi's works, such as Tahsil al-Sa'adah, as well as other secondary sources. The results indicate that Al-Farabi's concept of happiness has strong relevance in helping individuals in the digital age find the meaning of life and authentic happiness. Keywords: Happiness, Al-Farabi, Digital Age, Islamic Philosophy